Feasibility Study on Crack Detection of Pipelines Using Piezoceramic Transducers. (9th October 2013) - Du, Guofeng; Kong, Qingzhao; Lai, Timothy; Song, Gangbing
Abstract : Damage detection of pipelines is of great significance in terms of safety in the oil and gas industry. Currently, lead zirconate titanates (PZTs) are the most popular piezoceramic materials and show great potential in the applications of structural health monitoring. In this paper, the authors present a feasibility study on the crack detection and severity monitoring of pipelines using PZT transducers. Due to their electromechanical properties, the piezoceramic transducers can be either as an actuator or a sensor to generate or detect the stress wave. The active sensing approach was applied to monitor the crack severity of pipelines. The crack in the stress wave propagation path can be regarded as a stress relief, which reduces the received energy by the sensors. In the test, eight different operating conditions were tested in which one artificial crack was created ranging from 0 mm to 10.5 mm. A wavelet packet-based crack severity index was also built to quantitatively identify the pipeline damage condition at various crack depths.